ANALISIS ISIM TAFDHIL DALAM AL-QURAN JUZ KE 26 DAN METODE PEMBELAJARANNYA - Nisa, Fatimah Aulyia; Musni, Jaelani (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2023)
This research intends to know and analyze the isim of tafdhil found in Al-Qur'an juz 26. The research method used is library research or literature and data collection through a review of books, documents, literature, notes, and journals. Data collection using documentation techniques. Data analysis can be found from various sources by using aggregation techniques. The results of the study found 15 data containing isim tafdhil in Al-Qur'an juz 26. 7 of them occupy the syntactic function of khobar mubtada, 2 as mubtada, 4 as khobar kanna, 1 data as khobar inna, and 1 as is inna. Based on the type of structural pattern, 5 data do not start with alif lam, and 9 is tafdhil data that are based on isim nakiroh. And 1 data is based on is ma'rifah.